Sodium-glucose cotransporter 2 inhibitor dapagliflozin prevents ejection fraction reduction, reduces myocardial and renal NF-κB expression and systemic pro-inflammatory biomarkers in models of short-term doxorubicin cardiotoxicity - Quagliariello, V.; Canale, M. L.; Bisceglia, I.; Iovine, M.; Paccone, A.; Maurea, C.; Scherillo, M.; Merola, A.; Giordano, V.; Palma, G.; Luciano, A.; Bruzzese, F.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Anthracycline-mediated adverse cardiovascular events are among the leading causes of morbidity and mortality in cancer patients. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) exerts multiple cardiometabolic benefits in patients with/without type 2 diabetes, chronic kidney disease and heart failure with reduced and preserved ejection fraction. We hypothesized that the SGLT2i Dapagliflozin administered before and during doxorubicin therapy, could prevent cardiac dysfunction and reduce pro-inflammatory pathways in preclinical models. Methods: Cardiomyocytes were exposed to DOXO alone or combined to DAPA at 10 and 100 nM for 24h; cell viability, iATP and Ca++ were quantified; lipid peroxidation products (MDA and 4-HNA), NLRP3, MyD88 and cytokines were also analyzed through selective colorimetric and ELISA methods. Female C57Bl/6 mice were treated for 10 days with a saline solution or DOXO (2.17 mg/kg), DAPA (10 mg/kg) or DOXO combined to DAPA. Systemic levels of ferroptosis-related biomarkers, galectin-3, hs-CRP and pro-inflammatory chemokines (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL17-α, IL-18, IFN-γ, TNF-α, G-CSF, and GM-CSF) were quantified. After treatments, immunohistochemical staining of myocardial and renal p65/NF-kB was performed. Results: DAPA exerts cytoprotective, antioxidant and anti-inflammatory properties in human cardiomyocytes exposed to DOXO, by reducing iATP and iCa++ levels, lipid peroxidation and NLRP-3, MyD88 expression. Pro-inflammatory intracellular cytokines were also reduced. In preclinical models, DAPA prevented the reduction of radial and longitudinal strain and ejection fraction after 10 days of treatment with DOXO. A reduced myocardial expression of NLRP-3 and MyD-88 was seen in DOXO-DAPA group compared to DOXO mice. Systemic levels of IL-1β, IL-6, TNF-α, G-CSF and GM-CSF were significantly reduced after treatment with DAPA. Serum levels of galectine-3 and hs-CRP were strongly enhanced in DOXO group; contrary, their expression were reduced in DAPA-DOXO group. Troponin-T, BNP and NT-pro-BNP were strongly reduced in DOXO-DAPA group, revealing cardioprotective properties of SGLT2-i. Mice treated with DOXO and DAPA exhibited reduced myocardial and renal NF-kB expression. Conclusion: The overall picture of the study encourages the use of DAPA in primary prevention of cardiomyopathies induced by anthracyclines in cancer patients.